The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/lno.10932
|View full text |Cite
|
Sign up to set email alerts
|

Transport of dissolved black carbon from the Prydz Bay Shelf, Antarctica to the deep Southern Ocean

Abstract: Dissolved black carbon (DBC) is one of the largest pools of molecularly identifiable carbon in the ocean. In the deep ocean, DBC appears to persist for millennia, whereas it can be rapidly degraded by sunlight in surface waters. In Antarctica, the downward transport of dense shelf water (DSW) exports a massive volume of water to the deep Southern Ocean each year. If this sinking DSW is enriched in DBC, it may allow a route for DBC to escape degradation by sunlight in the surface ocean and become sequestered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 69 publications
(190 reference statements)
1
7
0
Order By: Relevance
“…The DBC concentrations in the deep water in the subtropical South Pacific (Fig. 1b ) are similar to those in CDW in the Southern Ocean (5.9 ± 0.8 µgC L −1 ), which were determined by the same BPCA method 42 . The decrease in the DBC concentration with deep-ocean meridional circulation (Fig.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The DBC concentrations in the deep water in the subtropical South Pacific (Fig. 1b ) are similar to those in CDW in the Southern Ocean (5.9 ± 0.8 µgC L −1 ), which were determined by the same BPCA method 42 . The decrease in the DBC concentration with deep-ocean meridional circulation (Fig.…”
Section: Resultssupporting
confidence: 59%
“…A major origin of DBC in CDW is related to the meridional overturning circulation and is therefore associated with North Atlantic Deep Water (NADW) and Antarctic Bottom Water (AABW) 41 . At least some of the DBC in AABW is reported to be derived from Antarctic shelf sediments 42 . The DBC concentrations in the deep water in the subtropical South Pacific (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previous studies have shown that the higher DBC concentrations in the upper 100 m of the SCS (avg. 0.97 ± 0.22 µmol-C L −1 , n = 79) (Fang et al, 2017) compared to those observed in Prydz Bay, Antarctica (0.75 ± 0.26 µmol-C L −1 , n = 17, Fang et al, 2018) should largely result from the enhanced emissions around the SCS.…”
Section: Abundance and Distribution Of Soot In The Northeastern South China Seamentioning
confidence: 68%
“…Around 34 ± 26% of biomass-generated BC (40-215 Tg yr −1 , including dissolved BC, i.e., DBC and PBC) gets into the oceans via river discharge (Jones et al, 2020). These reports indicate that the ocean is an important reservoir of BC (Masiello and Druffel, 1998;Fang et al, 2018). With an increase in BC emissions from the increase in both fossil fuel combustion and fires emissions, the riverine BC is expected to increase the refractory carbon pool in abyssal oceans (Cheng et al, 2008;Dittmar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This signal is transferred to DSW by deep convection in winter (Shadwick et al, 2014). As a result, DSW outflows are also likely enriched in organic matter, as observed in the dense overflows from the Ross Sea (Bercovici et al, 2017) and Cape Darnely and Prydz Bay in East Antarctica (Fang et al, 2018; Murakami et al, 2020).…”
Section: Discussionmentioning
confidence: 98%